# Simplify the expression 2√20 − 3√7 − 2√5 + 4√63.

We will use the concept of surds simplification in order to find the required answer.

## Answer: For the above expression, 2√5 + 9√7 is the simplified version in surds.

Let us see how we will use the concept of surds simplification in order to find the required answer.

**Explanation**:

For the above expression 2√20 − 3√7 − 2√5 + 4√63,

Let us simplify the surds first to get

2√20 = 2√(5 × 4) = 4√5

4√63 = 4√(9 × 7) = 12√7

Thus, applying these simplified versions to the expression

⇒ 2√20 − 3√7 − 2√5 + 4√63

= 4√5 − 3√7 − 2√5 + 12√7

= 4√5 − 2√5 + 12√7 − 3√7

= 2√5 + 9√7